A Systematic Literature Review of Mindfulness-Based Interventions for Intensive Care Unit Nurses: Impacts on Well-Being and Patient Care Quality - Laloan, Risty Mandane (Fakultas Ilmu Keperawatan Universitas Klabat, 2025)
This study systematically reviews the impact of mindfulness-based interventions (MBIs) on the well-being of intensive care unit (ICU) nurses and their effect on patient care quality. A systematic review of 12 peer-reviewed articles published between 2020 and 2025 was conducted. Findings revealed four major themes influencing ICU nurses’ well-being. First, MBIs consistently reduce stress and burnout, enhance emotional resilience, and improve emotional intelligence. Second, self-care practices, including mindful self-care and autonomy, support long-term health and career sustainability. Third, workplace stress remains a significant challenge, with adaptive coping strategies such as mindfulness and emotional regulation proving more effective than avoidance or detachment. Finally, workplace dynamics, particularly ethical dilemmas and organizational culture, strongly affect morale, retention, and the delivery of compassionate, high-quality care. Quantitative evidence supports these outcomes; for example, a Mindfulness-Based Stress Reduction (MBSR) program lowered burnout scores from 56.53 to 48.56, and a quasi-experimental study reported significant reductions in emotional exhaustion and depersonalization (p < 0.001). Despite these benefits, challenges such as time constraints, limited institutional support, and low engagement in formal mindfulness programs persist. A notable limitation is the heterogeneity of MBI designs and implementation protocols, highlighting the need for standardization and longitudinal research. To enhance accessibility, digital and hybrid mindfulness formats are recommended. This review emphasizes that institutional commitment is essential for integrating mindfulness into ICU settings, positioning MBIs as strategic approaches to promote nurse well-being and improve patient care quality. Penelitian ini secara sistematis meninjau dampak intervensi berbasis mindfulness (Mindfulness-Based Interventions/MBIs) terhadap kesejahteraan perawat di unit perawatan intensif (ICU) serta pengaruhnya terhadap kualitas asuhan pasien. Tinjauan dilakukan terhadap 12 artikel peer-reviewed yang diterbitkan antara 2020 hingga 2025. Hasilnya mengungkap empat tema utama yang memengaruhi kesejahteraan perawat ICU. Pertama, MBIs secara konsisten menurunkan stres dan burnout, meningkatkan resiliensi emosional, serta memperkuat kecerdasan emosional. Kedua, praktik perawatan diri, termasuk mindful self-care dan otonomi, mendukung kesehatan jangka panjang dan keberlanjutan karier. Ketiga, stres kerja tetap menjadi tantangan signifikan, di mana strategi koping adaptif seperti mindfulness dan regulasi emosi terbukti lebih efektif dibandingkan penghindaran atau pelepasan diri. Keempat, dinamika tempat kerja, khususnya dilema etis dan budaya organisasi, sangat memengaruhi moral, retensi, dan kemampuan perawat dalam memberikan asuhan yang penuh kasih dan berkualitas tinggi. Bukti kuantitatif mendukung temuan ini; misalnya, program Mindfulness-Based Stress Reduction (MBSR) menurunkan skor burnout dari 56,53 menjadi 48,56, dan studi kuasi-eksperimental menunjukkan penurunan signifikan pada kelelahan emosional serta depersonalisasi (p < 0,001). Meskipun demikian, tantangan tetap ada, seperti keterbatasan waktu, dukungan institusional yang minim, serta rendahnya partisipasi dalam program mindfulness formal. Keterbatasan utama penelitian adalah heterogenitas desain dan protokol implementasi MBIs, sehingga diperlukan standarisasi dan penelitian longitudinal. Untuk meningkatkan aksesibilitas, format digital dan hybrid diusulkan. Tinjauan ini menekankan pentingnya komitmen institusional dalam mengintegrasikan mindfulness di ICU sebagai strategi untuk meningkatkan kesejahteraan perawat sekaligus kualitas asuhan pasien.